Influence of wire feed rate on mechanical and microstructure characteristics of aluminum to galvanized steel laser brazed joint. (March 2019) - Narsimhachary, D.; Shariff, S.M.; Padmanabham, G.; Basu, A.
Graphical abstract: Highlights: AA5083-galvanised steel laser brazing (AlSi12 filler) resulted 6 μm intermetallic layer. Higher wire feed resulted higher joint strength. Joints and base Al-alloy exhibited comparable fatigue life at lower strain amplitude. Abstract: Laser brazing technique was employed to weld-braze 2 mm thick galvanized steel to 5083 aluminum alloy in flange joint configuration using 2 mm diameter solid AlSi12 (AA4047) filler wire. Experiments were performed at various wire feed rates (2.0–3.6 m/min) with constant laser power (3.5 kW), scan speed (2.5 m/min) and spot size (1.7 mm). The microstructural observation of the etched specimens under SEM showed cast structure at the brazed zone and a two-layered (planar and needle structured) interface towards the galvanized steel. HAZ was observed at the aluminum side. The selective Energy-dispersive X-ray spectroscopy (EDS) point analysis and X-ray diffraction technique were used to study the interface and the results confirmed that the planar and needle structures are comprised of ternary Alx -Fey -Siz and binary Alx -Fey intermetallic phases respectively. From hardness testing, both the base material, i.e., AA5083and galvanized steel are found to be harder than brazed zone. In case of nano-indentation testing, intermetallics have shown higher hardness values compared to base materials. The joint strength increased with increasing wire feed rate and recorded interfacial failure. Fatigue life of the laser brazed joints at lower stain amplitude is better with increasing wire feed rate and are in close range to the aluminum base material (AA5083) value. Fatigue tested specimens recorded brazed zone failure and revealed flow lines, intergranular cracking and typical fatigue striations.